On Three Criteria for the Assessment of the European Central Bank Legitimization in the Period of Crisis (Economic and Political Thought, 2013)
The European Central Bank (ECB) is perhaps the only technocratic institutionof the European Union, which gathers substantial authority during thecrisis. It is also perceived as an institution, which successfully stabilizes thecrisis in the euro area. The article is aimed at explaining the phenomenonof that bank during the crisis. First of all, the question whether the ECBactivities are appropriately legitimized is answered. Does the crisis-basedsituation authorize the Bank to go beyond the treaty mandate? Is the ECBreally efficient and does it improve its ‘utilitarian legitimization’? Does itremain a reliable institution, i.e. independent of the biggest states’ politicalinfluence? In addition, the author presents the Bank’s activities politicalrepercussions for the formulation of the ‘technocratic quasi-federation’ thatwas under the strong informal influence of the biggest member states.